PERANCANGAN APLIKASI E-LOGBOOK - Johanes Fernandes Andry; Andy Wijaya (ULTIMA InfoSys, 2020)
Based on research conducted on FKUI Specialist Education Program Participants (PPDS) it was found that a system that was implemented had not used computerized technology in the process of its daily activities. PPDS participants are prospective specialist doctors who will become experts and consultants in their respective specialties. PPDS is faced with a variety of cases, through emergency patients, inpatients, and outpatients so that they have the ability to treat patients.The use of this application is expected to simplify and process the logbook recording process so that it is faster and easier in gathering and managing data into information that can be utilized by stakeholders to improve services. Observations from research conducted at FKUI, it is known that the recording system using paper media is a tool used to record any data in the medical record resulting in frequent errors in the form of missing and damaged medical records. Therefore, the construction of computerized system design in order to reduce human error in the process of making reports and recording processes and keep the data from loss and damage of data.